The Relationship Between Market Orientation and Libyan Banks Performances : The Case Of Private And Public Small, Medium and Large-Sized Banks - G.M. Elkrghli , Dr. Sabri (Scientific Journal of University of Benghazi, 2026)
This paper aims to achieve four main objectives: (1). To measure the extent to which the Libyan banks embrace the market orientation concept. 2). To assess the Libyan banks performance from the participants point of view. (3) To determine the nature of the relationship between market Orientation applications and Libyan banks performance. (4). To determine whether there is a difference between these banks according to some selected variables: ownership (public / private), bank size (small /medium / large) participants' organisational position (owner, manager, employee, etc...). In terms of research methodology, (Narver and Slater's, 1990) construct vas used to measure market orientation adoption in Libyan banks. Banks performance was assessed based on participants' perception on most-common nine items scale taken from the marketing literature. A number of 592 questionnaires was distributed to participants in Libyan banks in Benghazi the second largest city in Libya. Out of this number, only 240 questionnaires have been retrieved with 124 proved to be valid for the data analysis stage. The key findings of the study is that the market orientation embracing is much higher in the private sector banks (small/ medium/ large) than the public one. The performance of private banks (small/ medium/ large) is also judged to be much better than the public banks. The results of the study also proved that there is a direct positive correlation between market orientation application and banks performance. This link is much stronger in the private sector. The study did not detect any differences among participants' views despite the divergence of their organisational positions. The scientific value of the paper is that it is the first research of this nature that touches this area of research with this level of analytical depth. Therefore, the paper enriches the marketing literature with these findings from Libya as one of the North African region countries. Practically, the paper demonstrates the importance of market orientation concept on improving the Libyan banks performance. Hence, Libyan Government, banks managers and employees should benefit from the results of this research. The paper concludes with the most important research challenges and suggests some future research directions.